The relationship between preoperative hemoglobin, albumin, lymphocyte, and platelet (HALP) score and right colon cancer surgery outcomes: a retrospective cohort study - Ay, Oğuzhan Fatih; Erol, Mehmet Fatih; Arıcı, Sinan; Karadağ, Mehmet (The European Research Journal, 2024)
Objectives: This study aims to investigate the association between the preoperative Hemoglobin Albumin Lymphocyte Platelet (HALP) score and surgical outcomes in right colon cancer patients. Methods: This retrospective cohort study included patients undergoing elective right colon adenocarcinoma surgery from January 2017 to June 2023 at Bursa Yuksek Ihtisas Training and Research Hospital. The HALP score, calculated from hemoglobin, albumin, lymphocyte, and platelet levels, aimed to predict perioperative morbidity through receiver operating characteristic (ROC) curve analysis. Results: The study involved 67 patients, mostly male with an average age of 68.28 years, undergoing 46 open and 21 laparoscopic surgeries. Although the HALP score’s cutoff value was established, it did not significantly predict perioperative morbidity (P>0.05). However, lower platelet counts (<318×103/L) and open surgery type correlated significantly with higher morbidity (P<0.05). Conclusions: This study reveals that the HALP score may not effectively predict perioperative morbidity in right colon cancer surgeries, highlighting platelet counts as a more promising marker. Our findings also confirm the increased morbidity associated with open surgeries, challenging existing assumptions and guiding clinical practice.